Annual clovers around the world: current status and future prospects - Nichols, Phillip Geoffrey Harwood; Smith, Gerald; Moot, Derrick; Ates, Serkan; Porqueddu, Claudio; Rios, Esteban; Louhaichi, Mounir; del Pozo, Alejandro; Kotze, Annemare; Humphries, Alan W; Ghamkhar, Kioumars; Ryan, Megan (Curran Associates, 2023)
This paper reviews the distribution and importance of annual clover (Trifolium) species for pasture and fodder production systems globally. Of the 158 recorded annual Trifolium species, 65.2% are endemic to the Mediterranean basin and surrounding areas, 14.6% to sub-Saharan Africa, 17.7% to the United States of America and 2.5% to Chile. Fourteen species have been commercialised, while other endemic and naturalised annual clovers are also utilised. Key species for self-regenerating pastures include T. subterraneum, T. michelianum and T. respinatum var. resupinatum, while major dual-purpose grazing and fodder species include T. incarnatum, T. vesiculosum, T. alexandrinum and T. respinatum var. majus. Less important commercial species include T. hirtum, T. squarrosum, T. nigrescens and T. cherleri. Australian scientists have also recently domesticated T. glanduliferum, T. spumosum, T. purpureum and T. dasyurum. The areas sown to annual clovers may increase in future years, due to increasing nitrogen (N) fertiliser costs, environmental concerns with N runoff. Climate change brings new challenges and opportunities for annual clovers. The forage plant genetic resource centres will be crucial for developing new adapted cultivars.